2011
DOI: 10.1128/jvi.05843-11
|View full text |Cite
|
Sign up to set email alerts
|

HepG2 Cells Expressing MicroRNA miR-122 Support the Entire Hepatitis C Virus Life Cycle

Abstract: The liver-specific microRNA miR-122 is required for efficient hepatitis C virus (HCV) RNA replication both in cell culture and in vivo. In addition, nonhepatic cells have been rendered more efficient at supporting this stage of the HCV life cycle by miR-122 expression. This study investigated how miR-122 influences HCV replication in the miR-122-deficient HepG2 cell line. Expression of this microRNA in HepG2 cells permitted efficient HCV RNA replication and infectious virion production. When a missing HCV rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
136
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(143 citation statements)
references
References 43 publications
4
136
1
1
Order By: Relevance
“…Chang et al (2008) showed that miR-122 could also enhance HCV replication in nonhepatic human embryonic kidney epithelial cells (HEK-293). Interestingly, expression of miR-122 has been shown to endow the ability of supporting efficient HCV RNA replication and infectious virion production in HepG2 cells (Narbus et al, 2011). Henke et al (2008) further uncovered a unique interaction of miR-122 with two binding sites in the 5′-UTR of the viral genome, which stimulates HCV translation by enhancing the association of ribosomes with the viral RNA.…”
Section: Mir-122 In Hcv Infectionmentioning
confidence: 99%
“…Chang et al (2008) showed that miR-122 could also enhance HCV replication in nonhepatic human embryonic kidney epithelial cells (HEK-293). Interestingly, expression of miR-122 has been shown to endow the ability of supporting efficient HCV RNA replication and infectious virion production in HepG2 cells (Narbus et al, 2011). Henke et al (2008) further uncovered a unique interaction of miR-122 with two binding sites in the 5′-UTR of the viral genome, which stimulates HCV translation by enhancing the association of ribosomes with the viral RNA.…”
Section: Mir-122 In Hcv Infectionmentioning
confidence: 99%
“…First of all, their poor or absent polarization biases HCV entry studies. New models such as the partially polarized and HCV-permissive HepG2 CD81/miR-122 cell line might help tackling this concern [112]. Furthermore, despite some controversy, it is generally accepted that the VLDL secretion is altered in the Huh-7 cell line [28,166].…”
Section: Host Cells For the Investigation Of Hcv Entrymentioning
confidence: 99%
“…miR-122 antagomir can inhibit replication of HCV, abundance of HCV core RNA, and expression of HCV nonstructural proteins (NS3 in CNS3 cells and NS3-5B in 9-13 replicon cells), in a time-and dosedependent manner [51,[60][61][62][63]. These findings are suggestive of miR-122 as a potential target for antiviral interventions in HCV patients [37,57,[64][65][66][67].…”
Section: Roles Of Mirnas In Virus-induced Hccmentioning
confidence: 64%
“…It is required for efficient replication of HCV in vitro and in vivo. Expression of miR-122 in HepG2 cells leads to efficient HCV RNA replication and infectious virion production [37]. When a missing HCV receptor was coexpressed with miR-122, HepG2 cells could efficiently facilitate viral entry and the entire life cycle of HCV.…”
Section: Roles Of Mirnas In Virus-induced Hccmentioning
confidence: 99%
See 1 more Smart Citation